Penerapan Ajaran Pembelaan Terpaksa Dalam Perkara Putusan Nomor 372/ Pid.B / 2020 /PN Pdg - Somarwane, Femmy Almendo; Hehanussa, Deassy Jacomina Anthoneta; Supusepa, Reimon (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The forced defense is a reason for eliminating the nature of breaking the law (wederrechtelijkheid or onrechtmatigheid), so the reason for eliminating the nature of a criminal act (strafuitsluitings-grond) is also said to be the reason for justifying or justifying actions that are generally criminal acts (rechtvaardigings-grond) called fait justi ficatief.Purposes of the Research: The purpose of this study is to analyze and explain the qualifications of forced defense in a criminal case, examine and explain the basic legal considerations in Decision Number 372/Pid.B/2020/PNPdg. The type of research used is normative juridical with qualitative analysis methods. The problem approach used is the conceptual approach, statutory approach and case approach. Sources of legal materials consist of primary, secondary and tertiary legal materials.Results of the Research: The results of the study show that in principle the Criminal Code indirectly provides an overview of forced defense that what is meant by forced defense is a defense of rights against injustice where a person is forced to commit a crime, can be forgiven because there was a violation of law that preceded the act. In making his decision, the judge has considerations consisting of juridical considerations and sociological considerations. Juridical considerations are judges' considerations that are based on juridical facts revealed in court and in the law that have been stipulated as matters that must be included in the decision. Sociological considerations are a judge's considerations that use approaches to background, socio-economic conditions and values that exist in society in making a decision.